2013
DOI: 10.1371/journal.pone.0081602
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Cellular Protective Factors of Rumen Epithelium in Goats Fed High Energy Diet

Abstract: Energy-rich diets can challenge metabolic and protective functions of the rumen epithelial cells, but the underlying factors are unclear. This study sought to evaluate proteomic changes of the rumen epithelium in goats fed a low, medium, or high energy diet. Expression of protein changes were compared by two-dimensional differential gel electrophoresis followed by protein identification with matrix assisted laser desorption ionisation tandem time-of-flight mass spectrometry. Of about 2,000 spots commonly detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 48 publications
4
20
0
Order By: Relevance
“…The mechanism(s) of translocation for toxic compounds may be favoured by impairment of the barrier function of the rumen epithelium (Emmanuel et al, 2007), depletion of protective factors (Hollmann et al, 2013) and increased luminal osmolality (Owens et al, 1998). Also, the chronic exposure to ethanol can increase the epithelial permeability and portal vein translocation of endotoxin (Enomoto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism(s) of translocation for toxic compounds may be favoured by impairment of the barrier function of the rumen epithelium (Emmanuel et al, 2007), depletion of protective factors (Hollmann et al, 2013) and increased luminal osmolality (Owens et al, 1998). Also, the chronic exposure to ethanol can increase the epithelial permeability and portal vein translocation of endotoxin (Enomoto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In a human colon adenocarcinoma cell line, acetate treatment in the pH range of 6.0 to 7.0 induced cell apoptosis rather than necrosis, while acetate treatment at pH 5.5 caused cell necrosis [7] . Additionally, a recent study conducted in growing goats showed that after feeding high grain diet for 6 wks, several chaperone proteins with important cellular protective functions were collectively down-regulated in ruminal epithelium, indicating an attenuated cell defense system [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted in goat and dairy cattle showed that a high grain diet impaired barrier functions of the rumen epithelium [23] , [24] , inflammation and caused other health problems in host animals [25] . Several chaperone proteins with important cellular protective functions in epithelial tissues were collectively down-regulated in response to high dietary energy supply, which indicates that energy-rich diets and the resulting acidotic insult may facilitate the impairment of rumen barrier function by attenuating their cell defense system [26] . However, no information exists about the underlying mechanism behind the disruption of protective functions of the hindgut epithelium in response to high grain diet to ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…Although excess oxidative stress is inferred from the literatures [22][23][24] , the responses of rumen epithelial cells to oxidative stress might be depressed during the first period in contrast to a short-term (17 days) SARA challenge in dairy cows 21 . These results also imply www.nature.com/scientificreports www.nature.com/scientificreports/ mitochondrial metabolic dysfunction (i.e., handling oxidative stress), suggesting greater rumen epithelial cell vulnerability to cellular damage by acidotic insult 25 .…”
Section: Discussionmentioning
confidence: 90%